New insights into the doubly charmed exotic mesons - Di Guo; Qin-He Yang; Ling-Yun Dai; A. P. Szczepaniak (European Physical Journal C: Particles and Fields)
Abstract Using effective Lagrangians constrained by the heavy quark spin symmetry and chiral symmetry, for the light quarks, we analyze the $$D^0 D^0π ^+,$$ D 0 D 0 π + , $$\bar{D}^0D^0π ^0$$ D ¯ 0 D 0 π 0 and $$D^0\bar{D}^{*0}$$ D 0 D ¯ ∗ 0 invariant mass spectra. Performing a simultaneous analysis of the doubly charmed and charm-anti-charm states gives further insights into the nature of the $$T^+_{cc}$$ T cc + and $$χ ^0_{c1}(3872),$$ χ c 1 0 ( 3872 ) , exotic hadrons. It is confirmed that both states should lie below their respective $$DD^*$$ D D ∗ / $$D\bar{D}^*$$ D D ¯ ∗ thresholds. Also, the contributions of the triangle and box diagrams are negligible.